Guidelines for the Development of Public Participation in Management of Bang Ra Kam Subdistrict Administrative Organization, Pho Thong District, Ang Thong Province - Tantibowon, Thitika; Wanthanang, Kamonwan (Lawarath Social E-Journal, 2025)
This research aimed to: 1. study the context of public participation; 2. compare public participation in management, divided by personal factors; and 3. examine the guidelines for developing public participation in management. There were two stages in the research methodology: 1. studied and compared public participation in management. The samples were 340 residents in Bang Ra Kam Sub-district Administrative Organization, Pho Thong District, Ang Thong Province selected by stratified sampling. A questionnaire with a reliability of 0.96 was used to collect data, and they were analyzed for percentage, mean, standard deviation, t-test, F-test, and LSD method; and 2. the guidelines for public participation in management were developed. The 12 informants selected by purposive sampling were interviewed, and the data were analyzed employing content analysis. The results revealed that: 1. the context of public participation in Bang Ra Kam Sub-district Administrative Organization was overall at a moderate level. The aspect with the highest mean was the residents’ participation in activities and the lowest one was the residents’ participation in development; 2. residents with different personal factors held different participation levels in the management with a statistical significance at .05; and 3. the guidelines for the development of public participation in the management included promoting community meetings to monitor and evaluate the implementation of projects. A satisfaction survey should be conducted to assess public opinions on the performance. Additionally, public feedback should be utilized to improve management strategies and to prepare reports on the implementation outcomes.